A Brief Study of Girish Karnad’s Play Hayavadana: Exploring the Pursuit of Completeness and Perfection (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The action of the play is dominated by the motif of completeness and perfection in life. Padmini wants to unite with a man who is perfect in body and mind and Hayavadana wants fulfilment in body because he has a horse head and human body. P. D. Nimsarkar, points out about Padmini’s story in the book titled Women in Girish Karnad’s Plays A Critical Perspective, “Padmini’s story is an attempt to break the natural order to seek her idea of perfection” (98). Whether it is Padmini or Hayavadana both of them try to get completeness and perfection.